Colonization, Growth and Productivity of Crustose Coralline Algae in Sunlit Reefs in the Atlantic Southernmost Coral Reef - Tâmega, Frederico T. S.; Figueiredo, Marcia A. O. (Frontiers in Marine Science, 2019)
One of the most important contributions of crustose coralline algae (CCA) to some coral reefs is their structural role in sunlit habitats, but in the Atlantic southernmost coral reef, Abrolhos, these algae are also important components of living communities covering larger areas than corals. Little is known about their competence in occupying reef space and consequently their ecological role. This work compared two CCA species along reef sites and habitats and their responses to different irradiance levels. To study colonization, epoxy discs were placed at four sites and three habitats (reef base, reef flat and reef edge). Crustose coralline individual pieces were glued onto epoxy discs and their relative growth was estimated. Productivity responses to irradiance levels found on reef habitats was measured on incubated samples. In general, CCA were less abundant than filamentous algae and non-calcareous crusts. Crustose algae showed no seasonal or spatial pattern in cover, contrasting with erect algae that differed in biomass among sites depending on season. Differences among habitats were only found for CCA. The dominant coralline Porolithon onkodes was more productive and grew faster than Lithophyllum stictaeforme at high irradiance level and both species were inhibited at low light. Dominance of P. onkodes in shallow and sunlit reefs was explained by its preference for high-light environments.